Exploring the service recovery landscape through the lens of a systemigram. (14th June 2019) - Harun, Ahasan; Prybutok, Gayle; Prybutok, Victor R.
Utilising Boardman soft systems methodology (BSSM) and its graphical systemic diagramming technique (the systemigram), this study improves the comprehension and identification of the complex interrelationships between relevant factors within the service failure/recovery domain. As a first step, we conducted a study of service recovery in the extant literature and identified the way situations associated with service failure and recovery was addressed. The second step was to synthesise the literature to propose the structure of the systemigram. This study contributes to the extant literature by doing the following: 1) identifying bottlenecks in the domain of service failure and recovery that complicate customer relations in the service industry; 2) providing academics and practitioners a comprehensive picture of the service recovery environment to provide a clear view of the factors that complicate service recovery; 3) equipping system analysts with a clear understanding of systemic issues related to service recovery; 4) identifying key insights and new research areas based on the scenes incorporated in a systemigram. Study findings and recommendations for future research are presented.